Comparative analysis of four nuclei in the human brainstem: Individual differences, left-right asymmetry, species differences - Baizer, Joan S.; Witelson, Sandra F. (Frontiers in Neuroanatomy, 2023)
We have studied the neurochemical organization of four nuclei of the human brainstem, the nucleus paramedianus dorsalis (PMD), the principal nucleus of the inferior olive (IOpr), the arcuate nucleus of the medulla (Arc) and the dorsal cochlear nucleus (DC). We compared these human brainstem nuclei with nuclei in other mammals including chimpanzees, monkeys, cats and rodents. We studied human cases from the Witelson Normal Brain collection using Nissl and immunostained sections, and archival Nissl and immunostained sections from other species. Overall, the results suggest several principles of human brainstem organization that distinguish humans from other species. First, there is significant individual variability in the size and shape of brainstem structures among humans. Second, there is left-right asymmetry in the size and appearance of nuclei, dramatically so in the Arc and IOpr. Third, in humans we found nuclei, e.g. the PMD and the Arc, not or rarely seen in several other species. Fourth, there are brainstem structures that are conserved across species but show major expansion in humans, for example the IOpr. Fifth, there are brainstem structures, for example the DC, that show major differences in cellular structure among species. Studying the functional correlates of, and the genetic contributions to, the brainstem characteristics we describe are important future research directions.